PENETAPAN KADAR TOTAL FENOLIK-FLAVONOID EKSTRAK ETANOL 70% KULIT BATANG TANDUI (Mangifera rufocostata Kosterm.) - Eka Fitri Susiani; Revita Saputri; Allisa Fanadia; Liana Fitriani Hasymi (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Tandui (Mangifera rufocostata Kosterm.) is a species of the genus Mangifera which is known to contain phenolic and flavonoid compounds and is one of the plants used as an alternative medicine by the people of South Kalimantan. The purpose of this study was to determine the total phenolic and flavonoid content of 70% ethanol extract of tandui bark. Qualitative analysis using phenolic and flavonoid phytochemical screening with 3% FeCl3, Mg-HCl reagents and Thin Layer Chromatography (TLC) with spot appearance 10% FeCl3 for phenolic and 5% AlCl3 for flavonoid compounds. Quantitative analysis using UV-Vis spectrophotometry, determination of total phenolic content using Folin-Ciocalteu reagent with gallic acid standard solution, while determination of total flavonoid content using AlCl3 reagent with quercetin standard solution. The results of identification of phenolic and flavonoid compounds by phytochemical screening and TLC showed that 70% ethanol extract of tandui bark contained phenolic and flavonoid. The results of the determination of the total phenolic content using UV-Vis spectrophotometry were 471.3126 mgGAE/g or 47.1312%, while the total flavonoid content was 872.075 mgQE/g extract or 87.2075%. Based on these results, it can be concluded that 70% ethanol extract of tandui bark contains secondary metabolites in the form of phenolics and flavonoids which have potential as medicine.